Pengaruh Pupuk Kompos Tandan Kosong Kelapa Sawit dan NPK Mutiara 16:16:16 terhadap Pertumbuhan serta Produksi Tanaman Terung Putih (Solanum melongena L.) - Putra, Satria Pratama Nugraha; Sulhaswardi, Sulhaswardi (Jurnal Agroteknologi, Agribisnis, dan Akuakultur, 2026)
The research was carried out at the Experimental Garden of the Faculty of Agriculture, Islamic University of Riau. The research was carried out for four months from September to December 2022. The aim of the research was to determine the effect of interactions and main factors of palm oil empty fruit bunches compost and NPK Mutiara 16:16:16 on the growth and production of white eggplant (solanum melongena L.). This study used a completely randomized design (CRD) factorial which consisted of two factors. The first factor was compost of Palm Oil Empty Fruit Bunches (K) consisting of 4 treatment levels, namely 0, 450, 900, and 1350 g/plot and the second factor Pupuk NPK Mutiara 16:16;16 (N) which consists of 4 treatment levels namely 0; 10; 20; and 30 g/plot to obtain 16 treatment combinations with 3 repetitions, so there are 48 experimental plots. Each plot consists of 4 plants by taking 2 plants as samples. Parameters observed were plant height, flowering age, harvesting age, number of fruits per plant, fruit weight per plant, fruit weight per fruit, fruit length per fruit and the amount of remaining fruit. Data were analyzed statistically and continued with a 5% honest significant difference test (HSD). The results showed that the interaction between palm empty fruit bunches compost and Mutiara NPK 16:16:16 had an effect on flowering age, harvesting age, number of fruits, weight per plant and amount of fruit left over. The best treatment was palm fruit bunch compost 1350 g/plot and NPK Mutiara 16:16:16 30 g/plot.